Assessment of Demographic Profile of Complete Denture Wearers and their Denture Hygiene Habits - Saba Parveen, Jawaid Sultan, Osama Shaikh, Muhammad Shoaib, Abdul Ghani Shaikh, Preesa Salman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the denture hygiene practices among elderly complete denture wearers. Subject and Methods: A total of 210 denture wearers in age range of 40 to 80 years were recruited in the study. All the study subjects were interviewed regarding their complete denture in terms of wearing duration, cleaning frequency, cleaning methods, continuous wearing and instruction regarding its hygiene. Results: Mean age of patients was 54.03+11.06 years, minimum 38 years and maximum 80 years. Males were found in majority 56.7% and females were 43.3%. Most of the cases i.e 38.1% wearing the denture form 1-3 years, followed by 29.0% wearing denture from less than 6 months. Around 53.3% were cleaning their denture once a day. Denture cleaning frequency and cleaning methods were statistically insignificant according to age and gender Conclusion: Brushing with dentifrice and without dentifrice was the method of choice for cleaning. Awareness programs should be carried out regarding proper cleaning methods and its cleaning frequency and others. Keywords: Denture Hygiene, Complete Denture Wearers, Habits.